Konsep Bahagia menurut Al-Qur’an Surat Ali Imron Ayat 14 - Suyatman, Suyatman; Supono, Eko; Sumiran, Sumiran (Lembaga Yasin AlSys, 2025)
This article explores the concept of happiness in the Qur’an based on Surah Ali Imran verse 14, which illustrates human inclinations toward worldly pleasures such as wealth, children, and the enjoyments of life. These pleasures are viewed as part of human nature (fitrah), yet they are temporary. The aim of this study is to uncover the meaning of true happiness as offered by the Qur’an through this verse and to analyze the distinction between illusory, world-oriented happiness and genuine happiness founded on tawhid values and an afterlife-oriented perspective. The research employs a qualitative approach through literature review, referencing authoritative tafsir works by scholars such as Ibn Kathir, Al-Maraghi, and Al-Qurtubi. The findings indicate that, in the Qur’anic view, happiness is not merely found in material fulfillment, but in the human ability to regard worldly pleasures as a means to draw closer to Allah. Therefore, true happiness is spiritual in nature, transcending worldly dimensions and oriented toward the Hereafter. This article contributes to enriching Islamic discourse on the essence of happiness in accordance with the guidance of the Qur’an.